A NEW TYPE OF NEIGHBOURHOODS USING SINE TOPOLOGY IN TRIGONOMETRIC TOPOLOGICAL SPACES (International Journal of Food and Nutritional Sciences, 2022)
In this article we introduce ts-neighbourhoods using Sin-open sets intrigonometric topological spaces. In addition, we examine their basic properties.Furthermore, we introduce and study the fundamental properties of ts*-Neighbourhoods intrigonometric topological spaces.